SLO Fundus Imaging Is the Most Sensitive Modality of Multimodal Imaging for Macular Microembolisms with Subtle Signs - Jang, L.; Herbort, C. P., Jr. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background. Microemboli of fat or other material into the terminal macular retinal circulation can be difficult to diagnose. We report 2 cases that showed subtle signs where SLO fundus imaging was most sensitive to precisely outline the limits of the inner retina infarction. Patients and Methods. Multimodal imaging analysis was performed including fundus photography, fluorescein angiography, indocyanine green angiography, Optical Coherence Tomography and SLO fundus imaging of 2 cases with suspected infarction of the inner retina. Cases. A 30-year-old man reported a grey central spot OD a few days after being squeezed between two cars with a sacrum fracture. Vision was 0.2 OD, and 1.0 OS. Examination was unremarkable and fluorescein angiography was normal. Octopus visual field showed a tiny central scotoma OD. Microperimetry showed decreased central sensitivity OD > OS. The only sign was a dark area on the SLO fundus picture indicating a subtle infarction of the inner retina (OD > OS) with nothing visible on the OCT. Resolution of lesions on the SLO picture ODS occurred in parallel with improvement of microperimetry and visual acuity. A 32-year-old woman suspected to take IV drugs had a sudden drop of vision to 0.4 OD and count fingers at 6 feet OS. Signs included macular hemorrhages and non perfusion on FA. The striking sign was a large dark area on the SLO picture precisely delineating the more extensive infarcted area of internal retina corresponding to OCT hyperreflectivity, visible in this case. Conclusions. Macular ischemia due to microemboli can show obvious fundus signs as hemorrhages, cotton wool spots and non perfusion or can present in a subclinical fashion. The SLO picture has a higher image contrast and higher resolution compared to conventional fundus photography and so can precisely delineate ischemic changes of the inner retina causing the unexplained visual loss.
Keywords: retinal microembolisms; SLO fundus imaging; retinal perfusion; macular ischemia; Purtscher-like retinopathy